Concurrent EPA and DHA Supplementation Impairs Brown Adipogenesis of C2C12 Cells - Ghnaimawi, Saeed; Baum, Jamie; Liyanage, Rohana; Huang, Yan (Frontiers in Genetics, 2020)
Maternal dietary supplementation of n-3 polyunsaturated fatty acids (n-3 PUFAs), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are considered to play positive roles in fetal neuro system development. However, maternal n-3 PUFAs may induce molecular reprograming of uncommitted fetal myoblasts into adipocyte phenotype, in turn affecting lipid metabolism and energy expenditure of the offspring. The objective of this in vitro study was to investigate the combined effects of EPA and DHA on C2C12 cells undergoing brown adipogenic differentiation. C2C12 myoblasts were cultured to confluency and then treated with brown adipogenic differentiation medium with and without 50µM EPA and 50µM DHA. After differentiation, mRNA and protein samples were collected. Gene expression and protein levels were analyzed by real-time PCR and western blot. General Proteomics analysis was conducted using mass spectrometric evaluation. The effect of EPA and DHA on cellular oxygen consumption was measured using a Seahorse XFP Analyzer. Cells treated with n-3 PUFAs had significantly less (P<0.05) expression of the brown adipocyte marker genes PGC1α, DIO2, and UCP3. Expression of mitochondrial biogenesis related genes TFAM, PGC1α, and PGC1β were significantly down-regulated (P<0.05) by n-3 PUFAs treatment. Expression of mitochondrial electron transportation chain (ETC) regulated genes were significantly inhibited (P<0.05) by n-3 PUFAs, including ATP5J2, COX7a1, and COX8b. Mass spectrometric and western blot evaluation showed protein levels of enzymes which regulate the ETC and Krebs cycle, including ATP synthase α and β (F1F0 complex), citrate synthase, succinate CO-A ligase, succinate dehydrogenase (complex II), ubiquinol-cytochrome c reductase complex subunits (complex III), aconitate hydratase, cytochrome c, and pyruvate carboxylase were all decreased in the n-3 PUFAs group (P<0.05). Genomic and proteomic changes were accompanied by mitochondrial dysfunction, represented by significantly reduced oxygen consumption rate, ATP production, and proton leak (P<0.05). This study suggested that EPA and DHA may alter the BAT fate of myoblasts by inhibiting mitochondrial biogenesis and activity and induce white-like adipogenesis, shifting the metabolism from lipid oxidation to synthesis.